Венчурний бізнес в Україні: сучасний стан та передісторія розвитку - Литвин, І. В.; Шевчук, К. С.; Lytvyn, Iryna; Shevchuk, Kateryna (Видавництво Львівської політехніки, 2022)
Проаналізовано сучасний стан та особливості розвитку венчурного підприємництва, досліджено структуру активів венчурних фондів в Україні. У статті виявлено етапи становлення та зародження венчурного бізнесу в Україні, проаналізовано відмінності функціонування венчурного бізнесу нашої країни від інших розвинених країн, визначено шляхи подальшого розвитку венчурної індустрії.

The current state of development of venture entrepreneurship was analyzed, the structure of assets of venture funds in Ukraine was investigated. The article highlights the stages of formation and birth of venture business in Ukraine, analyzes the differences between the functioning of venture business in our country and other developed countries, and determines the ways of further development of the venture industry. The article analyzes the advantages and disadvantages of venture capital investment for venture capital market participants. The main sources of funding for innovative developments in Ukraine have been identified. The stages of initiation and development of venture investment mechanisms in Ukraine through joint venture investment institutes are analyzed. The dynamics of the number of asset pooling companies and joint investment institutes and the structure of assets of venture capital investment institutes were studied. The authors investigate the problems of local venture business development in the pre-war period. Peculiarities of Ukrainian investment legislation are studied, and special attention is paid to the lack of specific legislation to stimulate the activity of venture capital institutes of joint investment. The article proposes to pay special attention to the role of the state and local authorities in the formation of a favorable climate and ecosystem for start-up entrepreneurship. Among the measures that need to be taken to preserve the local venture and startup industry in wartime, it is proposed to develop a legal framework to stimulate the functioning of venture business, a system of tax incentives to keep local startups in the local ecosystem, to form a multi-level system of training specialists for the innovation sphere, promote support from the international community of the local innovation sphere to support the competitiveness of the local market of innovation projects.
Venture business in Ukraine: current state and background of development
Keywords: венчурний бізнес; венчурні капіталовкладення; венчурні фонди; інститути спільного інвестування; venture business; venture capital investments; venture funds; joint investment institutes; 330.341.1